2013
DOI: 10.1177/0957650913505557
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of rural families in Kenya to technology changes

Abstract: Energy as a service is central to livelihoods. Services such as lighting, cooking and heating of water, space heating, cooling, information, communication, and earning a living are not always accessible without grid electricity and are critical to sustainable development. The acceptability of any new energy technology is very important if it has to be usable by the target group it is designed for. This paper documents a case study undertaken in rural areas of Kisumu, Kenya, to understand the behaviour of commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thermoacoustic engines can be integrated into efficient wood cooking stoves to provide electricity while cooking [39], but the output and efficiency have to date proven to be too low [32]. Recent social science studies have suggested that an ideal system would generate about 100 W of electrical energy and cost less than $100, and even 20 W conveys considerable benefits [40]. If research can increase the power output, the system could benefit the 3.3 billion who live in rural areas, of whom almost half use biomass for cooking but have no access to electricity [41].…”
Section: Externally Fired Gas Turbine (Efgt)mentioning
confidence: 99%
“…Thermoacoustic engines can be integrated into efficient wood cooking stoves to provide electricity while cooking [39], but the output and efficiency have to date proven to be too low [32]. Recent social science studies have suggested that an ideal system would generate about 100 W of electrical energy and cost less than $100, and even 20 W conveys considerable benefits [40]. If research can increase the power output, the system could benefit the 3.3 billion who live in rural areas, of whom almost half use biomass for cooking but have no access to electricity [41].…”
Section: Externally Fired Gas Turbine (Efgt)mentioning
confidence: 99%